"A Helping Hand over a Heavy Hand": Child Support Enforcement in the Era of COVID-19. Issue 5 (20th October 2022) - Vogel, Lisa Klein; Ros Pilarz, Alejandra; Cuesta, Laura; Caffrey, Genevieve
ABSTRACT: The COVID-19 pandemic forced human services agencies to adapt quickly to the economic realities faced by their customers. For child support agencies, the pandemic raised difficult questions about how strenuously agencies should enforce child support orders during periods of economic crisis and uncertainty. Drawing on interviews with agency and court staff, this study explores staff's perceptions of pandemic-related effects on parents' abilities to work and pay, how and why enforcement practices changed during the pandemic, and changes staff expect to persist. Agency staff reported a pause on enforcement at the pandemic's outset, followed by leniency, flexibility, caution, and empathy in their practices.